(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2025)
Traditional identity management systems rely on centralized servers that store personally identifiable information (PII), creating vulnerabilities such as data breaches, unauthorized access, and identity theft. With increasing digital transformation, secure identity verification is critical across sectors including finance, governance, healthcare, and e-commerce. Blockchain offers a decentralized, immutable, and transparent alternative for secure identity management. This paper investigates blockchain-driven identity management models, evaluates decentralized identifiers (DIDs), explores privacy-preserving cryptographic mechanisms, and surveys the challenges in developing scalable identity systems. A prototype conceptual framework for a distributed identity management system is proposed. Experimental analysis from literature demonstrates improved security, reduced authentication latency, and enhanced user control over personal data. The study concludes that blockchain-based identity management is essential for next-generation digital ecosystems, although interoperability and regulatory alignment remain major obstacles.